resenha do livro: Conflicts and Conspiracies: Brazil e Portugal 1750-1808 - Iglesias, Francisco (Revista de História, 2023)
Resenha do livro: Conflicts and Conspiracies: Brazil & Portugal 1750-1808. Cambridge: At the University Pres, 1973, 289p.